Democratisation of wellbeing: stakeholder perspectives on policy priorities for improving national wellbeing through paid employment and adult learning. Issue 4 (4th July 2018) - Daniels, Kevin; Connolly, Sara; Ogbonnaya, Chidiebere; Tregaskis, Olga; Bryan, Mark L.; Robinson-Pant, Anna; Street, John
ABSTRACT: Recent policy initiatives in the UK have heightened the degree to which wellbeing can be considered a political construct: The acceptance of different policy options for wellbeing depends on the extent to which those options are responsive to popular wellbeing concerns. Drawing on the views of over 400 people gathered through a variety of methods and across the UK, we outline different stakeholder views of what wellbeing is and the priorities that stakeholders believe should be addressed to improve wellbeing. We draw out the implications for reframing policy debates around wellbeing, the practice of career guidance, academic debates around identified wellbeing priorities, and the best means of developing a policy and a practice-oriented and stakeholder-responsive approach to researching wellbeing.